2012
DOI: 10.1259/dmfr/30200901
|View full text |Cite
|
Sign up to set email alerts
|

Dose reduction of cone beam CT scanning for the entire oral and maxillofacial regions with thyroid collars

Abstract: Objective: The aim of this study was to evaluate the influence of thyroid collars on radiation dose during cone beam CT (CBCT) scanning. Methods: Average tissue-absorbed dose for a NewTom 9000 CBCT scanner (Quantitative Radiology, Verona, Italy) was measured using thermoluminescent dosemeter chips in a phantom. The scans were carried out with and without thyroid collars. Effective organ dose and total effective dose were derived using International Commission on Radiological Protection 2007 recommendations. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 20 publications
1
20
0
1
Order By: Relevance
“…Therefore, leadequivalent and lead thyroid shields are as effective as each other in CBCT imaging. Studies in adult phantoms have shown 0.35-mm lead equivalence is most effective; 18,19 however, this was the only thickness of thyroid shield tested. The better performance of Design 2 for the superior slice may have been owing to a better neck adjustment, and the lateral aspects of the neck are shielded using this design, since the neck straps also contain shielding materials.…”
Section: Thyroid Shielding Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Therefore, leadequivalent and lead thyroid shields are as effective as each other in CBCT imaging. Studies in adult phantoms have shown 0.35-mm lead equivalence is most effective; 18,19 however, this was the only thickness of thyroid shield tested. The better performance of Design 2 for the superior slice may have been owing to a better neck adjustment, and the lateral aspects of the neck are shielded using this design, since the neck straps also contain shielding materials.…”
Section: Thyroid Shielding Resultsmentioning
confidence: 95%
“…Adult dosimetry laboratory studies have shown a dose reduction ranging from 44% to 72%. 18,19,27 The average thyroid dose can be compared with the study by Theodorakou et al, 11 since a similar phantom, same machine, exposure factors and FOV were used. The average thyroid dose obtained without a thyroid shield was higher than that recorded by Theodorakou et al 11 This difference may be explained by the different location of the TLDs.…”
Section: Thyroid Shielding Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Protective thyroid collars are recommended for both dental intraoral and CBCT radiographic procedures, because their use reduces radiation exposure to the thyroid gland by about 50%. [34][35][36] Leaded aprons should include thyroid collars.…”
Section: The Image Gently In Dentistry Campaignmentioning
confidence: 99%